MATHEMATICAL MODELLING AND & SIMULATION OF THRESHER OPERATION IN PALM OIL MILL - Shanti Faridah, Salleh; Shareena, Saree; Khairuddin, Sanaullah; Afrasyab, Khan; Robiah, Yunus; Marini, Sawawi; NORDIANA, RAJAEE; Norzafirah Azriah, MOHD FADZLI; Mohammed, Haji Alhaji (Penerbit UMT Universiti Malaysia Terengganu, 2019)
The development of the palm oil mill has been on a downward trend recently due to world economic recession, the technological input for oil extraction is the factor that contributes to this production setback in the industry. Therefore, there a need to develop an advanced technology that will enable a spontaneous increase in the oil extraction rate (OER). This study is aimed at the development of the technological mode of operation for the thresher unit which has seldom been neglected over the years. Computational numerical analysis has been selected for this study focusing on the stickiness and centrifugal force of the thresher. The resistance force has been obtained through the calculation of all the loads obtains from the thresher body as well as from its revolution per minute (rpm). The calculation on the impact of the opposite force on the internal and external part of the thresher was conducted. It has proposed to verify gravity of forces of the fruit spikelet has on the thresher. The result from this study will be useful in the design of an efficient process for achieving high oil extraction rate in the palm oil mill Industry.